ANALISA PERBANDINGAN KUAT TEKAN BETON ANTARA PENGGUNAAN AGREGAT KASAR TAYU DAN PAMOTAN - Masta'in, Masta'in (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2023)
The compressive strength of concrete is determined by setting the ratio of cement, coarse aggregate, fine aggregate and water. The use of water is used to provide chemical action in hardening concrete, excess water can facilitate work but can reduce the strength of concrete. The compressive strength of concrete produced using tayu coarse aggregate is higher than pamotan coarse aggregate with a characteristic compressive strength that occurs at fc 22 .08, while the compressive strength used coarse aggregate was fc 21.52. So the results show that the concrete test with coarse aggregate from tayu has a greater concrete compressive strength value. The slump value in fresh concrete as an indicator of feasibility and mix quality in fresh concrete uses the minimum value of the required slump value. because the higher the slump produced in fresh concrete will affect the compressive strength of the concrete made.